Comparative Study of Risk Factors Among the Male and Female Patients with Acute Myocardial Infarction Admitted in CCU of Sahid Gangalal National Heart Centre - Raut, Roshan; K C, Man Bahadur; Sharma, Deewakar; Rajbhandari, Sujeeb; Baidhya, Sajan Gopal; Dhungana, Murari; Pradhan, Manish; Shrestha, Pragati; Bajracharya, Monica (Nepalese Heart Journal, 2017)
The role of major cardiovascular risk factors in the development of coronary artery disease (CAD) is well established and is fairly similar in both sexes. However, CAD is markedly more common in male than in female, and this is due to more risk factors, especially smoking and dyslipidemia, in male. In this study, we aim to investigate the five major risk factors as defined by ACC-AHA namely, advancing age, smoking, hypertension, diabetes and dyslipidemia, in the MI patients admitted in CCU, SGNHC from Jan 1 to June 30th 2008 and to compare whether the association of those risk factors with CAD risk is similar in male and female. There were altogether 283 MI patients, Male 208 (73%) and Female 75 (27%). Advancing age was the most common comprising 85.2% followed by smoking 55.5%, Hypertension 48.1%, Dyslipidemia 47% and Diabetes 24.7%. Smoking, dyslipidemia and advancing age were significantly more common in male. Male patients have significantly more risk factors than female. There was trend towards the greater number of high total cholesterol and low HDL in male patients. Advancing age (Male 45 yrs, Female 55 yrs) is the commonest risk factor of CAD. Smoking and dyslipidemia (especially high total cholesterol and low HDL) are significantly more common in male which might have contributed markedly to the excess CAD risk in males.